The best American short stories 1998 : - Keillor, Garrison (Houghton Mifflin Company, 1998)
Edited by beloved storyteller Garrison Keillor, this year's volume promises to be full of humor, surprises, and, as always, accomplished writing by new and familiar voices. The preeminent short fiction series since 1915, The Best American Short Stories is the only volume that annually offers the finest works chosen by a distinguished best-selling author.